Evolution and Characteristics of Peruvian Biomedical Publications, 1985 – 1996 - Alarcón, Jorge (1996)
A study about the evolution and main characteristics of scientific articles related to research conducted in Peru publish both in national and, international journals between 1985 - 1993, was made. We identified 2412 scientific articles published in 32 national journals, and 297 articles in 134 international journals. There was found that national journals had published sporadically, and the amount of articles increased only 12% in 8 years. In addition, the autor’s features, the type of scientific articles and the topics studied, are described. Finally some explanations about the factors associated to evolution and characteristics observed, are given.